ANALISA SIFAT FISIS DAN MEKANIS KOMPOSIT HIBRID SERAT JUTE/KARBON YANG DIBUAT DENGAN METODE VACUUM INFUSION SEBAGAI ALTERNATIF BAHAN HELM - Venditias Yudha; Ferriawan Yudhanto; Joko Waluyo (Scientific Journal of Mechanical Engineering Kinematika, 2023)
The application of natural fibers in the hybrid laminated composite with synthetic fibers potentially reduces the production cost of composite products. Jute fibers have gained interest because of their properties such as biodegradability, low cost, and high cellulose content. This study investigated the effect of chemical treatment on the woven jute fiber to determine its impact on the mechanical properties of jute/carbon hybrid composites. The chemical treatment with alkalization and then bleaching is considered for jute woven fibers before manufacturing hybrid composite. Four layers using two woven jute fibers and two woven carbon fibers were fabricated by the vacuum infusion method. Physical properties were carried out by Fourier transform infrared and x-ray diffraction to treat jute fiber. Tensile and flexural tests are carried out according to ASTM standards D638 and D790, respectively. Composite hybrid R-JKJK and P-JKJK have fulfilled the criteria to be used as an alternative helmet material.